TI_GERICHTE 35.2022.5 vom 11. Mai 2022 , Corretta l'entità della rendita di invalidità assegnata all'assicurata - TI Tribunale d'appello (2022)
Corretta l'entità della rendita di invalidità assegnata all'assicurata